Is the First Urinary Albumin Creatinine Ratio (ACR) in Women With Suspected Preeclampsia a Prognostic Factor for Maternal and Neonatal Adverse Outcome? A Retrospective Cohort Study. Issue 1 (March 2018) - Elia, E.G.; Robb, A.O.; Hemming, K.; Price, M.J.; Riley, R.D.; French-Constant, A.; Denison, F.C.; Kilby, M.D.; Morris, R.K.; Stock, S.J.
Abstract : ( Acta Obstet Gynecol Scand . 2017;96(5):580–588) Preeclampsia can result in severe maternal complications and perinatal mortality. The albumin to creatinine ratio (ACR) is an independent prognostic factor for maternal and neonatal adverse outcomes in suspected preeclampsia. This retrospective cohort study aimed at determining the prognostic value of baseline first ACR in predicting maternal and neonatal adverse outcomes in women with suspected preeclampsia.